Eating Behaviors in Healthy Young Adult Twin Pairs Discordant for Body Mass Index. (August 2019) - Berntzen, Bram J.; Jukarainen, Sakari; Bogl, Leonie H.; Rissanen, Aila; Kaprio, Jaakko; Pietiläinen, Kirsi H.
Abstract: We aimed to study the eating behavioral traits that associate with body mass index (BMI) among BMI-discordant twin pairs. This cross-sectional study examined self-reported eating behaviors in 134 healthy young adult twin pairs (57 monozygotic [MZ] and 77 same-sex dizygotic [DZ]), of whom 29 MZ and 46 DZ pairs were BMI discordant (BMI difference ≥ 3 kg/m 2 ). In both MZ and DZ BMI-discordant pairs, the heavier co-twins reported being less capable of regulating their food intake optimally than their leaner co-twins, mainly due to 'frequent overeating'. Furthermore, the heavier co-twins reported augmented 'disinhibited eating', 'binge-eating scores' and 'body dissatisfaction'. The twins agreed more frequently that the heavier co-twins (rather than the leaner co-twins) ate more food in general, and more fatty food, in particular. No significant behavioral differences emerged in BMI-concordant twin pairs. Overeating — measured by 'frequent overeating', 'disinhibited eating' and 'binge-eating score' — was the main behavioral trait associated with higher BMI, independent of genotype and shared environment.